2020
DOI: 10.1002/ijc.33285
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic circulating levels of sex hormones and survival in esophageal adenocarcinoma

Abstract: Sex hormonal differences may contribute to the strong male predominance in esophageal adenocarcinoma (EAC), but whether sex hormone levels influence survival in EAC is unstudied. Our study aimed to assess associations between prediagnostic sex hormone levels and survival in EAC. In a population-based cohort study, 244 male EAC patients from the Janus Serum Bank Cohort in Norway were followed up through 2018. Associations between prediagnostic serum levels of 12 sex hormone measures and disease-specific mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
2
1
Order By: Relevance
“…Recently, Xie, S-H et al found that an increased disease-specific mortality with lower SHBG levels and higher FSH levels in male EAC patients without surgical treatment. No clear associations were observed for dehydroepiandrosterone sulphate, LH, prolactin, testosterone, 17-OH-progesterone, progesterone, E2, androstenedione, testosterone:estradiol ratio or free testosterone index [46]. In our study, there was no correlation between sex hormones level and pathological features.…”
Section: Correlation Between Serum Sex Hormones Levels and Pathologic...contrasting
confidence: 86%
“…Recently, Xie, S-H et al found that an increased disease-specific mortality with lower SHBG levels and higher FSH levels in male EAC patients without surgical treatment. No clear associations were observed for dehydroepiandrosterone sulphate, LH, prolactin, testosterone, 17-OH-progesterone, progesterone, E2, androstenedione, testosterone:estradiol ratio or free testosterone index [46]. In our study, there was no correlation between sex hormones level and pathological features.…”
Section: Correlation Between Serum Sex Hormones Levels and Pathologic...contrasting
confidence: 86%
“…A research study suggested that hormones may be associated with high incidence rate of EAC in men [47]. Androgen receptor (AR) Scientific Programming is also commonly present in human tissues and is also seen in esophageal cancer [48]. Barrett's esophagus, a precancerous lesion of esophagus, has higher circulating levels of dihydrotestosterone (DHT) and testosterone than normal [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…The causes for this gender difference in esophageal cancer are still unclear. Different exposure to high‐risk factors such as alcohol and tobacco, 20 , 21 hormonal influences, 22 , 23 and abdominal obesity, particularly in men, 24 probably led to this male predominance.…”
Section: Discussionmentioning
confidence: 99%